MEAN OF «QUALITY MANAGEMENT SYSTEM» AND ITS MANAGEMENT METHODS FOR CARGO AIRLINE COMPANY DEVELOPMENT - Гасимов, А. А.; Мільцов, В. Є. (Science-based technologies, 2019)
This article aims to consider the effectiveness and benefits of improving management in aviation enterprises by creating, implementing and developing Integrated Management Systems (including the Quality Management System). As noted earlier, at the basis of the creation and development of management systems, the requirements and regulations of international standards should be laid down so that compliance with the requirements of aviation regulations (ICAO, IATA, EASA, etc.) effectively harmonizes with the projects and procedures developed in accordance with such guidelines and requirements like: International Standard ISO:9001-2015 (Quality Management System Standard); Document ICAO-9859 (Safety Management System Manual); Document ICAO-8973 (Aviation Security Manual); ISO:45001-2018, previously known as OHSAS-18001 (Occupational Health and Safety Management System); İSO:14001-2004 (Environmental Management), etc. The integration of aviation safety management systems with Quality Management System procedures provides an orderly approach to monitoring work processes and procedures aimed at identifying hazards and risks to flight safety and their consequences, as well as to improve and develop the activities of any airline, which provides internal and external cargo airline company. Saying that the Integrated Management System is based on the basis of international ISO standards, it should be noted that the standards are only a “skeleton”, a reinforcement that needs to be filled with specific creative solutions. The effectiveness of the future system depends on the expediency and progressiveness of these decisions. And this is ensured by the knowledge, experience, professionalism of the management and staff, the arsenal of methods they own, the ability to see the result behind the chain of industrial relations, the ability to establish these relationships both in the production environment as a whole and in each workplace.